Pemanfaatan Laboratorium Komputer dalam Meningkatkan Pengetahuan Dasar Komputer Siswa Madrasah Aliyah Swasta - Masdaudi, Fitri Rahmah; Jailani, M. Syahran; Fadhil, Muhammad (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to describe the use of computer laboratories, identify the challenges faced by Information and Communication Technology (ICT) teachers in utilizing these laboratories, and understand the efforts made by the school to address these challenges. The study seeks to enhance students' foundational computer knowledge through the effective use of computer laboratories.Method – The research employs a descriptive method with a qualitative approach, conducted at the Private Islamic Senior High School of Perguruan Hidayatul Islamiyah in Kuala Tungkal. The study's participants include the principal, the vice principal for facilities and infrastructure, the computer laboratory coordinator, ICT teachers, and students. Data collection techniques involve observation, interviews, and documentation, with data validity ensured through triangulation. The data analysis process includes data reduction, data presentation, and drawing conclusions.Findings – The findings demonstrate that computer laboratories significantly enhance students' basic computer skills at the Private Islamic Senior High School of Perguruan Hidayatul Islamiyah in Kuala Tungkal. Students gain practical experience, reinforcing theoretical knowledge, while collaborative tasks in the lab foster problem-solving and engagement. However, challenges such as outdated equipment and internet issues limit the full potential of laboratory use. Despite these obstacles, ICT teachers incorporate lab activities effectively to create an engaging learning environment. Research Implications – Although facilities meet minimum standards (Indonesian Ministry of Education Regulation No. 24 of 2007), there is potential for improvement. Regular updates to equipment, improved internet access, and teacher training would enhance learning outcomes. This context highlights the importance of equipping madrasah students with essential digital skills for their academic and professional.